2022
DOI: 10.1002/bab.2388
|View full text |Cite
|
Sign up to set email alerts
|

2‐Amino thiazole derivatives as inhibitors of some metabolic enzymes: An in vitro and in silico study

Abstract: The thiazole derivatives are desirable compounds in the evaluation of their biological activities such as antiprotozoal antibacterial, antifungal, antituberculosis. Considering the medical application potential of 2‐amino thiazole compounds, we aimed to determine the effects of 2‐amino thiazole derivatives on the activities of carbonic anhydrase I–II isoenzymes, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Among the chemicals we used in our study, 2‐amino‐4‐(4‐chlorophenyl)thiazole compound ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The earlier study also found that a large number of synthesized derivatives such as thiazole-based compounds, 4H-1,2,4-triazole derivatives, Nbenzyl(oxotriazinoindole), 2,4-thiazolidinediones, benzothiazolone-based carboxylic acid inhibited AR [25,26]. The study finds the inhibition potencies of 3 and 6 were higher than thiazole-based compounds, 4H-1,2,4triazole derivatives and coumarin-thiosemicarbazone hybrids [11,37,39].…”
Section: Figure 3 Activity%-[derivative] Graphs Of the Two Best Inhib...mentioning
confidence: 84%
See 1 more Smart Citation
“…The earlier study also found that a large number of synthesized derivatives such as thiazole-based compounds, 4H-1,2,4-triazole derivatives, Nbenzyl(oxotriazinoindole), 2,4-thiazolidinediones, benzothiazolone-based carboxylic acid inhibited AR [25,26]. The study finds the inhibition potencies of 3 and 6 were higher than thiazole-based compounds, 4H-1,2,4triazole derivatives and coumarin-thiosemicarbazone hybrids [11,37,39].…”
Section: Figure 3 Activity%-[derivative] Graphs Of the Two Best Inhib...mentioning
confidence: 84%
“…For the determination of compounds' in vitro effects, the enzyme activities were assayed in the presence of at least five various compound concentrations. The control measurement having no compound was assumed as 100% and measurements in the presence of compounds were calculated as % activity [26]. Data were drawn as Activity%-[compound] graphs, and IC50 values were calculated from the equations of these graphs [27].…”
Section: Determination In Vitro Inhibition Effectsmentioning
confidence: 99%
“…Among the compounds, 2-amino-4-(4-chlorophenyl)thiazole compound exhibited the best inhibition against hCA I and 2amino-4-(4-bromophenyl)thiazole compound exhibited the best inhibition against hCA II, AChE, and BChE. [17] There are many studies in the literature on carbonic anhydrase and cholinesterase enzymes, which have a thiazole structure. [18][19][20][21] For this purpose, this study aimed to present new alternative drug candidates to the literature by synthesizing thiazole-derived compounds and then investigating their enzyme inhibition (AChE, BChE, hCA I, hCA II) and antioxidant activities.…”
Section: Introductionmentioning
confidence: 95%